2006
DOI: 10.1021/la052969c
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Nanotribology by AFM:  A Novel Universal Calibration Platform

Abstract: The quantitative determination of friction forces by atomic force microscopy (AFM) in nanotribology requires the conversion of the output voltage signal of the sector area-sensitive photodiode to force using (a) the torsional spring constant of the cantilever and (b) the lateral sensitivity of the photodiode. Many existing methods provide calibration factors with large errors and suffer from poor reproducibility. We report on the fabrication, validation, and application of a new, universally applicable standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 85 publications
3
74
0
Order By: Relevance
“…Atomic Force Microscopy: The contact-mode AFM measurements were carried out with a NanoScope III multimode AFM (Digital Instruments/Veeco, Santa Barbara, CA) using silicon nitride tips/cantilevers in ambient atmosphere, as described earlier [26].…”
mentioning
confidence: 99%
“…Atomic Force Microscopy: The contact-mode AFM measurements were carried out with a NanoScope III multimode AFM (Digital Instruments/Veeco, Santa Barbara, CA) using silicon nitride tips/cantilevers in ambient atmosphere, as described earlier [26].…”
mentioning
confidence: 99%
“…However, more recently, some investigators have reported that the so-called wedge method has found wide acceptance for the calibration of the torsional stiffness of AFM cantilevers. [23][24][25][26] Regarding the relationship between the surface roughness and the frictional coefficient, some investigators have reported significant positive correlations between the two on the surfaces of middle-finger 27 and footwear materials, olefins, 30 and plate bricks. 31 However, no significant relationship has been reported between the surface roughness and frictional behavior with regard to the surfaces of a selfassembled monolayer, silicon ruler, and metal evaporated tape through AFM measurements (torsional resonance mode) as well as on the surfaces of Cu, Al, Zn, and Sn through pin-on-plate measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been reported 24,26 that the torsional spring constant ␣ may increase with load; our method avoids this concern.…”
Section: ͑14͒mentioning
confidence: 94%
“…Because of this, several methods have been developed for measuring or calculating the cantilever spring constants. [12][13][14][15][17][18][19][20][21][22][23][24][25][26][27] Usually, the cantilever is calibrated for the specific equipment used, 7,9,19,[28][29][30][31][32][33] but the accuracy obtained for spring constant values frequently is low. Due to the uncertainty in material properties and cantilever thickness, 26 the calculated spring constants k can have large relative errors of 40%-45% and 30%-35% ͑assuming uniform thickness͒ for V-shaped and single beam cantilevers, respectively.…”
Section: Methodsmentioning
confidence: 99%